The Role of Foster Parents in Forming Children's Social Interactions - Mhd Fadlan Choiri; Mutiawati Mutiawati (Yayasan Letiges Konsultan Sosial, 2024)
This research explores the significant role of foster parents in shaping the social interaction of children in Al Washliyah Orphanage, Binjai City. Using a qualitative method with a descriptive approach, the study involved in-depth observations, direct interviews with foster parents and foster children, as well as analysis of related documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results revealed that foster parents adopt various strategies, including advice-giving, encouragement to interact, and organizing social activities, to improve children's social skills. However, the results still showed that some foster children had difficulties in interacting and tended to be withdrawn, highlighting the need for additional methods and more modern adaptations. These findings emphasize the importance of innovation in parenting approaches to support the social development of children in orphanages more effectively and sustainably.